HIV and adolescents' educational attainment in South Africa: Disentangling the effect of infection in children and household members - (:unkn) unknown (My University, 2018)
BACKGROUND. Many empirical studies have assessed the effect of adults' HIV infection on their livelihood. However, the effect of children's HIV status on their educational outcomes during adolescence has not been adequately investigated. OBJECTIVES. The study aims to evaluate the effect of household members' HIV infection and that of children on their educational outcomes (school enrolment and progression) during adolescence. METHODS. Waves 1 to 4 of the South African National Income Dynamics Study panel data collected between 2008 and 2015 were used. Analytical samples contained data for 8 835 adolescents aged 10-19 years. Analysis involved the use of descriptive statistics, logistic and linear regression as well as Oaxaca and Ransom decomposition methods. RESULTS. Of the study sample, 7 176 were currently in school and 636 were not. HIV infection had no effect on adolescent school enrolment. Adolescent HIV infection significantly reduced their school progress index by about 8.41. The explanatory variables explained 18% of the adolescents' school progress gap associated with HIV infection. The unexplained gap might have been attributable to stigmatisation and/or unobserved morbidity associated with adolescents' HIV infection. CONCLUSION. Adolescent HIV infection affects their school progression. Education support should be targeted directly at HIV-infected children instead of targeting families with infected parents only.
Keywords: African Research